2021
DOI: 10.1002/ieam.4524
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the ecological status of lakes and rivers from Canada's oil sands region

Abstract: We synthesize the information available from the peer‐reviewed literature on the ecological status of lakes and rivers in the oil sands region (OSR) of Canada. The majority of the research from the OSR has been performed in or near the minable region and examines the concentrations, flux, or enrichment of contaminants of concern (CoCs). Proximity to oil sands facilities and the beginning of commercial activities tend to be associated with greater estimates of CoCs across studies. Research suggests the higher m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 194 publications
(543 reference statements)
3
45
0
Order By: Relevance
“…Particulates were also emitted after installation of the precipitator at SBM and following the opening of the Syncrude Mildred Lake (SML) mine [5]. Since the opening of the SBM and SML facilities, they have been expanded and new operations have also opened [8]. As the industrial development intensified, studies also expanded and identified the influence of a broader set of sources affecting the environment, including haul road, petroleum coke, and other fugitive dust emissions associated with SBM and SML, but also with the opening of the new mines, technological differences among the facilities, including the opening of in situ operations, and changes at facilities over time [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Particulates were also emitted after installation of the precipitator at SBM and following the opening of the Syncrude Mildred Lake (SML) mine [5]. Since the opening of the SBM and SML facilities, they have been expanded and new operations have also opened [8]. As the industrial development intensified, studies also expanded and identified the influence of a broader set of sources affecting the environment, including haul road, petroleum coke, and other fugitive dust emissions associated with SBM and SML, but also with the opening of the new mines, technological differences among the facilities, including the opening of in situ operations, and changes at facilities over time [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Since the opening of the SBM and SML facilities, they have been expanded and new operations have also opened [8]. As the industrial development intensified, studies also expanded and identified the influence of a broader set of sources affecting the environment, including haul road, petroleum coke, and other fugitive dust emissions associated with SBM and SML, but also with the opening of the new mines, technological differences among the facilities, including the opening of in situ operations, and changes at facilities over time [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The work also shows the greatest loading of CoCs to the environment typically occurs in the minable region within ~25 km of the original bitumen upgrading facilities at SML and SBM, e.g., [10,25,28], but the influence of industrial activity on CoCs is not always apparent [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations